Outcome of open abdominal management following military trauma. Issue 8 (30th March 2018) - Pengelly, S; Berry, J E A; Herrick, S E; Bowley, D M; Carlson, G L
Abstract: Background: Temporary abdominal closure (TAC) is increasingly common after military and civilian major trauma. Primary fascial closure cannot be achieved after TAC in 30 per cent of civilian patients; subsequent abdominal wall reconstruction carries significant morbidity. This retrospective review aimed to determine this morbidity in a UK military cohort. Methods: A prospectively maintained database of all injured personnel from the Iraq and Afghanistan conflicts was searched from 1 January 2003 to 31 December 2014 for all patients who had undergone laparotomy in a deployed military medical treatment facility. This database, the patients' hospital notes and their primary care records were searched. Results: Laparotomy was performed in a total of 155 patients who survived to be repatriated to the UK; records were available for 150 of these patients. Seventy-seven patients (51·3 per cent) had fascial closure at first laparotomy, and 73 (48·7 per cent) had a period of TAC. Of the 73 who had TAC, two died before closure and two had significant abdominal wall loss from blast injury and were excluded from analysis. Of the 69 remaining patients, 65 (94 per cent) were able to undergo delayed primary fascial closure. The median duration of follow-up from injury was 1257 (range 1–4677) days for the whole cohort. Nine (12 per cent) of the 73 patients who underwent TAC subsequently developed an incisional hernia, compared with ten (13 per cent) of the 77 patients whose abdomen was closed at the primary laparotomy ( P = 1·000). Conclusion: Rates of delayed primary closure of abdominal fascia after temporary abdominal closure appear high. Subsequent rates of incisional hernia formation were similar in patients undergoing delayed primary closure and those who had closure at the primary laparotomy. Abstract : Most closed; hernia rates similar to primary closure